Methicillin resistance is not a predictor of severity in community‐acquired Staphylococcus aureus necrotizing pneumonia—results of a prospective observational study. (12th December 2012) - Sicot, N.; Khanafer, N.; Meyssonnier, V.; Dumitrescu, O.; Tristan, A.; Bes, M.; Lina, G.; Vandenesch, F.; Vanhems, P.; Etienne, J.; Gillet, Y.
<x xml:space="preserve">Abstract</x> Clin Microbiol Infect 2013; 19: E142–E148 Abstract Staphylococcal necrotizing pneumonia (NP) is a severe disease associated with Panton–Valentine leucocidin (PVL). NP was initially described for methicillin‐susceptible Staphylococcus aureus (MSSA) infection, but cases associated with methicillin‐resistant S. aureus (MRSA) infection have increased concomitantly with the incidence of community‐acquired MRSA worldwide. The role of methicillin resistance in the severity of NP remains controversial. The characteristics and outcomes of 133 patients with PVL‐positive S. aureus community‐acquired pneumonia (CAP) were compared according to methicillin resistance. Data from patients hospitalized for PVL‐positive S. aureus CAP in France from 1986 to 2010 were reported to the National Reference Centre for Staphylococci and were included in the study. The primary end point was mortality. Multivariate logistic modelling and the Cox regression were used for subsequent analyses. We analysed 29 cases of PVL‐MRSA and 104 cases of PVL‐MSSA pneumonia. Airway haemorrhages were more frequently associated with PVL‐MSSA pneumonia. However, no differences in the initial severity or the management were found between these two types of pneumonia. The rate of lethality was 39% regardless of methicillin resistance. By Cox regression analysis, methicillin resistance was not found to be a significant independent predictor of mortality at 7 or 30 days (p 0.65 and p 0.71, respectively). Our study demonstrates that methicillin resistance is not associated with the severity of staphylococcal necrotizing pneumonia.